MCP mobile commerce passport - Vergel de Dios, Jose Timoteo S. (2002)
From bulky precious metals and the barter system to plastic cash cards and e-commerce, man's mode of payment has greatly evolved. Be it the introduction of coins, bills, banks, checks, or automated teller machines, a trend can be noted in the stages of this continuous evolution process. This trend revolves around man's need for faster, more secure, and more convenient financial transactions. Mobile commerce (m-commerce) may be tagged as the next step in this evolution process. It merges the efficiency and broad range of e-commerce with the convenience, inter-connectivity, and speed of mobile communication devices such as cellular phones. The Philippines, being one of the top subscribers to mobile services, particularly short message services (SMS), is an ideal test bded for the development of such a system. Mobile Commerce Passport (mcP) focuses on the research and development of a system to be used as a platform for m-commerce. The system is designed to handle financial transactions through SMS. It aims to make billing, payment, and record-keeping processes a lot faster, flexible, and convenient for the business entities, financial institutions, and consumers. A special feature is the ability to pay remotely, TV shopping for example. It also aims to reduce security problems such as fraud and theft.
Thesis (B.S. Computer Science)--University of the Philippines, Diliman.
Keywords: Mobile commerce; Electronic commerce -- Technological innovations; Electronic commerce -- Security measures; Mobile commerce passport; e-Commerce.